The Influence of Cigarette Smoke Exposure on the Copper Concentration in the Serum Depending on the Use of Menopausal Hormone Therapy. (14th August 2017) - Jasińska-Starczewska, Maria; Szydłowska, Iwona; Mroczek, Bożena; Laszczyńska, Maria; Chlubek, Dariusz; Kemicer-Chmielewska, Ewa; Chełstowski, Kornel; Karakiewicz, Beata; Ciećwież, Sylwester; Starczewski, Andrzej
Abstract : This study evaluated the effect of menopausal hormone therapy (MHT) on serum concentration of copper in postmenopausal women depending on passive or active exposure to tobacco smoke or lack thereof. The study included healthy postmenopausal women aged 42–69 years, who used (n = 76 ) or did not use (n = 76 ) MHT. Salivary cotinine and serum copper concentrations were determined in all the study subjects. Salivary cotinine exceeded 14 ng/ml in 14 women from the MHT group (18.5%) and in 16 controls (21.1%). Up to 41 (27%) study subjects had serum copper above the upper normal limit (1.17 mg/l). No correlation was found between salivary cotinine and serum copper in women with cotinine concentrations <14 ng/ml, and these two parameters correlated weakly in subjects with cotinine >14 ng/ml. Salivary concentration of cotinine increased with serum copper level in the MHT group, but not in the controls; smokers using MHT presented with significantly higher serum copper than nonsmokers. These findings imply that MHT does not affect serum concentration of copper in women who are not exposed to tobacco smoke. However, MHT seems to contribute to unfavorable increase in serum copper in passive and active smokers.